Pengaruh Product Quality terhadap Buying Decision melalui Electronic Word of Mouth (EWOM) - Bella Denisya; Estri Mahani , Septiana Ayu (UNISBA Press, 2024)
Abstract. This study focuses on Product Quality, Buying Decision, and Electronic Word Of Mouth (E-WOM). The purpose of the study is to determine the relationship between product quality, Buying decision, electronic word of mouth (e-wom) at Mixue Cihampelas, Bandung City. This study uses descriptive and verification research with a quantitative approach with a purposive sampling technique. The population in this study were consumers who had made purchases at Mixue Cihampelas, Bandung City. The sample used was 150 respondents. Data analysis in this study was descriptive analysis using simple linear regression analysis and hypothesis testing using T-test analysis. The results showed that product quality has a positive and significant effect on buying decisions, and E-WOM also has a positive effect on buying decisions. In addition, Product Quality has a positive effect on E-WOM, indicating that consumers who are satisfied with Product Quality tend to give positive reviews. Further analysis shows that E-WOM mediates the relationship between Product Quality and buying decisions, strengthening the influence of Product Quality on buying decisions. In conclusion, improving Product Quality and managing E-WOM is very important to drive consumer buying decisions, providing practical insights for brand managers in designing effective marketing strategies in the food and beverage industry. Abstrak. Penelitian ini berfokus pada Product Quality, Buying Decision, dan Electronic Word Of Mouth (E-WOM). Tujuan dari penelitian ialah untuk mengetahui Hubungan antara product quality, Buying decision, electronic word of mouth (e-wom) pada mixue Cihampelas Kota Bandung. Penelitian ini menggunakan Penelitian deskriptif dan Verifikatif dengan pendekatan kuantitatif dengan teknik purposive sampling. Populasi pada penelitian ini ialah konsumen yang pernah melakukan pembelian pada Mixue Cihampelas kota Bandung. Sampel yang digunakan 150 responden. Analisis data pada penelitian ini ialah analisis deskriptif menggunakan analisis regresi liner sederhana serta pengujian hipotesis menggunakan analisis uji T. Hasil penelitian menunjukkan bahwa product quality memiliki pengaruh positif dan signifikan terhadap buying decision, dan E-WOM juga berpengaruh positif terhadap buying decision. Selain itu, Product Quality berpengaruh positif terhadap E-WOM, menunjukkan bahwa konsumen yang puas dengan Product Quality cenderung memberikan ulasan positif. Analisis lebih lanjut menunjukkan bahwa E-WOM memediasi hubungan antara Product Quality dan buying decision, memperkuat pengaruh Product Quality terhadap buying decision. Kesimpulannya, peningkatan Product Quality dan pengelolaan E-WOM sangat penting untuk mendorong buying decision konsumen, memberikan wawasan praktis bagi pengelola merek dalam merancang strategi pemasaran yang efektif di industri makanan dan minuman.